Root Systems Research for Bioinspired Resilient Design: A Concept Framework for Foundation and Coastal Engineering - Stachew, Elena; Houette, Thibaut; Gruber, Petra (Frontiers in Robotics and AI, 2021)
The continuous increase in population and human migration to urban and coastal areas leads to the expansion of built environments over natural habitats. Current infrastructure suffers from environmental changes and their impact on ecosystem services. Foundations are static anchoring structures dependent on soil compaction, which reduces water infiltration and increases flooding. Coastal infrastructure reduces wave action and landward erosion but alters natural habitat and sediment transport. On the other hand, root systems are multifunctional, resilient, biological structures that offer promising strategies for the design of civil and coastal infrastructure, such as adaptivity, multifunctionality, self-healing, mechanical and chemical soil attachment. Therefore, the biomimetic methodology is employed to abstract root strategies of interest for the design of building foundations and coastal infrastructures that prevent soil erosion, anchor structures, penetrate soils, and provide natural habitat. The strategies are described in a literature review on root biology, then these principles are abstracted from their biological context to show their potential for engineering transfer. After a review of current and developing technologies in both application fields, the abstracted strategies are translated into conceptual designs for foundation and coastal engineering. In addition to presenting the potential of root-inspired designs for both fields, this paper also showcases the main steps of the biomimetic methodology from the study of a biological system to the development of conceptual technical designs. In this way the paper also contributes to the development of a more strategic intersection between biology and engineering and provides a framework for further research and development projects.